From source identification to preferential interventions: Determinants of a workplace mental health promotion program to control workplace stress among health care workers based on a qualitative study - Masoume Zeinolabedini; Mohammad Esmaeil Motlagh; Alireza Heidarnia; Ghodratollah Shakerinejad (PLoS ONE, 2026)
Occupational stress among healthcare workers (HCWs) is increasing due to the development of healthcare services and increased occupational sensitivity. The aim of this study was to identify the determinants of a workplace mental health promotion program for stress management among HCWs. Data for this qualitative study were obtained through semi-structured interviews and focus groups. Data analysis was conducted using a directed content analysis approach, grounded in the PRECEDE-PROCEED model (PPM) and the Job Demands-Resources (JD-R) model. It was found that workplace stress has both individual and environmental (mainly organizational) origins. In the second phase of the program, ten subcategories were identified as effective factors in reducing employee stress in three categories: predisposing, enabling, and reinforcing factors. In the final step, in order to create changes and implement interventions, it was revealed that there is a need to formulate or revise managerial and structural policies in the organization and empower employees to improve interpersonal skills and manage workplace stress. Also, Non- occupational factors, Cognitive factors, Supervisory function, Personality characteristics, and Personal context of the employee were identified as new subcategories in the PPM to investigate work stress. Workplace stress has different sources and dimensions. Therefore, it is necessary to consider a combined and multi-level approach, including individual, social, organizational, and educational factors, for the mental health promotion program in the workplace. In this regard, the conceptual model proposed in this study can be a roadmap for researchers and employers to control the stress of HCWs and other employees.